2022
DOI: 10.1007/s11356-021-17560-w
|View full text |Cite
|
Sign up to set email alerts
|

The environmental impact of industrialization and foreign direct investment: empirical evidence from Asia-Pacific region

Abstract: Environmental degradation has been the main distress in recent years due to the drastic effect of climate change. To determine the gone thorough impact of industrialization and foreign direct investment on environmental degradation, this study utilized panel data of 55 countries of the Asia-Pacific region from 1995 to 2020 and it applies an autoregressive distributed lag (ARDL) model. The results showed that FDI, in general, has a significant negative impact on the environment and causes to increase in methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 63 publications
4
39
0
4
Order By: Relevance
“…Naturally, these gases are in a balanced state. Due to industrialization, these gases became unbalanced, transforming them into poisonous gases that deteriorated the state of the atmosphere and are now driving climate change through global warming [7,8]. Global warming has concentrated the heat in the atmosphere, damaged the ozone layer, and is making the temperature rise, which causes water vapors and heavy rain, which causes rising sea levels and flooding [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, these gases are in a balanced state. Due to industrialization, these gases became unbalanced, transforming them into poisonous gases that deteriorated the state of the atmosphere and are now driving climate change through global warming [7,8]. Global warming has concentrated the heat in the atmosphere, damaged the ozone layer, and is making the temperature rise, which causes water vapors and heavy rain, which causes rising sea levels and flooding [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature identified industrialization [22], urbanization [23], some foreign direct investment [24,25], and economic growth [26,27] as being responsible for environmental deteriorations, while some researchers identified that individual human activities are also responsible for environmental deterioration. For instance, Zhang et al [5] and Appannagari [28] argued that individuals' activities, such as extraction of natural resources to fulfill their basic needs, i.e.…”
Section: Climate Awareness and Environment Qualitymentioning
confidence: 99%
“…Many researchers have explored the relationship amid economic growth and CO 2 . Beside it, Ahmed et al ( 2022 ) focused a relationship between China’s economic growth and CO 2 emissions. The results show that on one side, rapid industrialization increases the development process, but on the other hand, it deteriorates ecological excellence.…”
Section: Review Of Literaturementioning
confidence: 99%